Aggregatibacter actinomycetemcomitans and Fusobacterium nucleatum in subgingival biofilms from Brazilian patients with and without periodontal disease: comparison of two detection methods - de João Malheiros, Veruska (2018)
Objective: A comparative detection of strains of A. actinomycetemcomitans and F. nucleatum directly from subgingival samples was performed by culture and polymerase chain reaction (PCR) methods. Methods: Fifty patients with chronic periodontitis (P) and 50 healthy patients (S) were evaluated. Subgingival samples were collected from periodontal pockets and gingival sulcus. Bacterial culture was performed on trypticase soy-horse serum- bacitracin-vancomycin agar and incubated in anaerobiosis. Bacterial identification was done by biochemical methods of carbohydrate fermentation and by PCR. Results: By culture method, of the 50 samples of periodontitis, 9 (18%) were positive for A. actinomycetemcomitans isolating 17 strains. Also, of these samples, 10 (20%) were positive for F. nucleatum isolating 19 strains. Of the 50 samples from healthy patients, only 1 (2%) was positive for A. actinomycetemcomitans, obtaining 2 strains, and 12 (24%) positive for F. nucleatum with 18 strains. Differences were observed in the detection of A. actinomycetemcomitans among the three pairs of primers used, for periodontal pocket and gingival sulcus samples: primer AA, 96% and 86%; primer FU, 48% and 42%; and primer ASH, 24% and 6%. The percentages of detection for F. nucleatum of samples from P and S were: primer FN-5047, 36% and 18%; and primer 505-S, 8% for both samples collected. Strains of A. actinomycetemcomitans biotype II were the most prevalent. Conclusions: The PCR method was more sensitive and specific in the bacterial detection than the culture.